Visible Islam in modern Turkey - Ozdemir, Adil.; Frank, Kenneth; SpringerLink (Online service) (London : Palgrave Macmillan UK, 2000)
Visible Islam in Modern Turkey presents a rich panorama of Islamic practices in today's Turkey. The authors, one a Muslim and one a Christian, introduce readers to Turkish Islamic piety and observances. The book is also a model for Muslims, for it interprets the foundations of Islam to the modern mind and shows the relevance of Turkish Islamic practices to modern society. Packed with data and insights, it appeals to a variety of circles, both secular and traditional.
Keywords: Philosophy; Religion; Islam; Religion -- Philosophy